Biotechnological potential of Ulva ohnoi epiphytic bacteria: enzyme production and antimicrobial activities - Hmani, I.; Ktari, L.; Ismail, A.; EL Bour, M. (Frontiers in Marine Science, 2023)
Epiphytic bacteria live in association with Ulva macroalgae and have a crucial role on the growth and morphogenesis of the host and allow the good development of algae. Those bacteria are able to synthesize enzymes and biomolecules for targeted uses in industry and biotechnology. Culturable Ulva associated bacteria were isolated and identified with 16S rRNA gene sequences. Enzymatic activity screening was undertaken for 8 enzymes: amylase, hemolysis, DNAse, cellulase, lecithinase, lipase, gelatinase and chitinase production. The antimicrobial activity of Ulva epibionts was evaluated against 7 pathogenic bacteria: Escherichia coli, Vibrio anguillarum, Vibrio alginoliticus, Pseudomonas aeruginosa, Aeromonas hydrophila, Salmonella typhymurium, Staphylococcus aureus, and one yeast Candida albicans. Antibiotic resistance of isolated strains was determined for 15 commonly used antibiotics. The phylogenetic analysis showed that the isolated bacteria belong to three phyla: Proteobactreia (8), Firmicutes (4) and Actinobacteria (3). Enzymatic activity screening demonstrated that 67% of the isolated strains produce at least one enzyme. While 60% of isolates displayed antimicrobial activity against at least one pathogenic strain. All fifteen Ulva ohnoi epibionts were resistant to at least 7 commonly used antibiotics. Results highlight the biotechnological potential of Ulva ohnoi associated bacteria that can be source for the extraction of targeted and valuable biomolecules useful in several industrial fields.